2015
DOI: 10.1007/s11356-015-4205-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of salt-affected soils: a review of processes, applicability, and the impact of climate change

Abstract: Soil salinization affects 1-10 billion ha worldwide, threatening the agricultural production needed to feed the ever increasing world population. Phytoremediation may be a cost-effective option for the remediation of these soils. This review analyzes the viability of using phytoremediation for salt-affected soils and explores the remedial mechanisms involved. In addition, it specifically addresses the debate over plant indirect (via soil cation exchange enhancement) or direct (via uptake) role in salt remediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(128 citation statements)
references
References 113 publications
0
96
0
2
Order By: Relevance
“…Salinization is particularly widespread in arid and semiarid parts of the world (Figure 1a; De Pascale & Barbieri, 1997;D'Odorico & Porporato, 2006;FAO et al, 2012;Fischer et al, 2008;Lombardini, 2006;Rohades et al, 1992), where it represents a major threat for subsistence agriculture and food security (Casey, 1972;Godfray et al, 2010;Goodin et al, 1990;Raheja, 1966). Additionally, climate change, land use modifications, groundwater overabstraction, and erroneous irrigation practices are expected to further exacerbate the problem in the next decades (Jesus et al, 2015;Pankova & Konyushkova, 2014;Pitman & Läuchli, 2002;Qadir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Salinization is particularly widespread in arid and semiarid parts of the world (Figure 1a; De Pascale & Barbieri, 1997;D'Odorico & Porporato, 2006;FAO et al, 2012;Fischer et al, 2008;Lombardini, 2006;Rohades et al, 1992), where it represents a major threat for subsistence agriculture and food security (Casey, 1972;Godfray et al, 2010;Goodin et al, 1990;Raheja, 1966). Additionally, climate change, land use modifications, groundwater overabstraction, and erroneous irrigation practices are expected to further exacerbate the problem in the next decades (Jesus et al, 2015;Pankova & Konyushkova, 2014;Pitman & Läuchli, 2002;Qadir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…According to Macci et al (2013), industrialization during the past decades caused an ever-increasing reliance on petrochemicals, and as a consequence, many sites have been significantly contaminated with petroleum and the petroleum-byproducts (Jesus et al, 2015 andGennadiev et al, 2015). This is especially more serious around the petroleum and petrochemical complexes and refineries in the countries producing these materials and generally the overall industrialized regions.…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained in this study has shown that higher concentrations of TPH and TPAH were obtained from the sludge (65,326.8 and 4,190.598mg/kg) than that of the soil (8,756.148 and 311.569 mg/kg). The presence of these hydrocarbons contributed to the measured differences in the physicochemical characteristics of the samples which leaches into the waterways (755.291 and 22.746 mg/L) via the soil where it accumulates and enters the food chain (Table 1).…”
Section: Resultsmentioning
confidence: 62%
“…Operational activities around petroleum refineries like several in the Niger Delta region of Nigeria are renowned for its cumulative oil spills due to large oil deposits [3][4][5]. These sites are poorly and most often never investigated to know the extent of petroleum hydrocarbon contamination and as a result there is high possibility of accumulation of these pollutants in the food chain by their consumption in drinking water, fish and crops, which could pose a risk to human and other terrestrial and aquatic life [6][7][8]. Crude oil pollution from spills and poor waste disposal affect the physicochemical properties of soils with sometimes also the build-up of high concentrations of heavy metals in the affected sites [9].…”
Section: Introductionmentioning
confidence: 99%